A Pair of Atypical KAS III Homologues with Initiation and Elongation Functions Program the Polyketide Biosynthesis in Asukamycin. Issue 19 (10th March 2022) - Yan, Xiaoli; Zhang, Jun; Tan, Hongqun; Liu, Zhihao; Jiang, Kai; Tian, Wenya; Zheng, Mengmeng; Lin, Zhi; Deng, Zixin; Qu, Xudong
Abstract: β‐Ketoacyl‐ACP synthase III (KAS III) is a class of important C−C bond‐forming enzymes that mostly catalyze the initiation of polyketide and fatty acid biosynthesis. In this study, we elucidated an unusual polyketide synthase (PKS) system that involves two unique KAS IIIs (AsuC3 and C4) in the biosynthesis of the upper triene chain of asukamycin. Significantly, AsuC3 and C4 have both initiation and iterative elongation activity, while being functionally biased toward the elongation and initiation steps, respectively. Mutational analysis revealed that their catalytic activities rely on the catalytic triad Cys‐His‐Asn. Unlike other KAS IIIs, AsuC3 and C4 are very promiscuous and can accept various lengths of acyl‐CoAs with either cyclic, branched or linear acyl moieties. By cooperation with the permissive ketoreductase (AsuC7) and dehydratase (AsuC8/C9), a large variety of polyenes can be efficiently synthesized. This study significantly broadens the understanding of KAS IIIs and polyketide biosynthesis. Abstract : KAS IIIs are known to be involved in the initiation step of polyketide and fatty acid biosynthesis. In vitro reconstitution of the upper triene chain of asukamycin unveils two highly unusual KAS IIIs which both exhibit initiation and iterative elongation activity. Together with the permissive ketoreductase and dehydratase, these C−C bond‐forming enzymes can synthesize a large variety of polyenes.